2023
DOI: 10.1002/tpg2.20371
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the salt overly sensitive pathway in Prunus: Identification and characterization of NHX, CIPK, and CBL genes

Abstract: Salinity is a major abiotic stress factor that can significantly impact crop growth, and productivity. In response to salt stress, the plant Salt Overly Sensitive (SOS) signaling pathway regulates the homeostasis of intracellular sodium ion concentration. The SOS1, SOS2, and SOS3 genes play critical roles in the SOS pathway, which belongs to the members of Na+/H+ exchanger (NHX), CBL‐interacting protein kinase (CIPK), and calcineurin B‐like (CBL) gene families, respectively. In this study, we performed genome‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…Transcriptional regulation plays a vital role in enhancing plant salt stress tolerance, as transcription factors control the expression of stress‐responsive genes that contribute to the plant's response to stress (Acharya et al, 2023). Amongst the gene families responsive to salt stress, CBL and NHX hold significant importance (Acharya et al, 2023). By identifying the CqCBL and CqNHX families in quinoa, we can establish a crucial groundwork for understanding the involvement of Cqtrihelix in salt stress regulation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptional regulation plays a vital role in enhancing plant salt stress tolerance, as transcription factors control the expression of stress‐responsive genes that contribute to the plant's response to stress (Acharya et al, 2023). Amongst the gene families responsive to salt stress, CBL and NHX hold significant importance (Acharya et al, 2023). By identifying the CqCBL and CqNHX families in quinoa, we can establish a crucial groundwork for understanding the involvement of Cqtrihelix in salt stress regulation.…”
Section: Resultsmentioning
confidence: 99%
“…Transcriptional regulation plays a vital role in enhancing plant salt stress tolerance, as transcription factors control the expression of stress-responsive genes that contribute to the plant's response to stress (Acharya et al, 2023). Amongst the gene families responsive to salt stress, CBL and NHX hold significant importance (Acharya et al, 2023). By identifying the CqCBL and CqNHX families in quinoa, we can establish a crucial groundwork for understanding the involvement of Cqtrihelix in salt stress regulation.…”
Section: Comprehensive Analysis Of Two Quinoa Saltresponsive Gene Fam...mentioning
confidence: 99%
“…CML and CDPK genes are also involved in the regulation of the salt overly sensitive (SOS) pathway in plants during their response to salt stress [34]. CML and CDPK genes can interact with key proteins in the SOS pathway and could regulate the activity and function of these proteins [35]. For example, in the SOS pathway, CBL could activate CIPK in response to salt stress and thus could promote ion excretion.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated concentrations of NaCl in the soil lead to a decrease in water potential and diminished water availability, resulting in osmotic stress in plants ( Acosta-Motos et al, 2017). Acharya et al (2023) conducted genomewide identifications and phylogenetic analyses of key genes, including NHX, CIPK, and CBL, associated with the plant salt overly sensitive (SOS) signaling pathway across six Rosaceae species. The investigation revealed that intron-rich CIPKs in Rosaceae and Arabidopsis traced their origins back to algae CIPKs and those found in early plants, suggesting the evolutionary development of intron-less CIPKs from their intron-rich counterparts.…”
Section: Soil Constraints and Salinity Tolerancementioning
confidence: 99%